546 A Longitudinal Case History of Skin Cancer Presentations from One of the UK's Longest Surviving Renal Transplant Patients. (19th August 2022) - Rela, M; Sarginson, J; Rickard, R
Abstract: Introduction: The immunosuppression required by solid-organ transplant patients not only increases their risk of severe infections but also pre-disposes them to post-transplant malignancy, with skin cancers being the most frequent type. We present a longitudinal history of skin cancers in a patient who received their kidney transplant as a child and has been on immunosuppression for 50 years. Case Report: The patient developed renal failure at 12 years of age and received a living donor renal transplant in 1970. He developed his first skin cancer in 2004, 34 years later. To date he has had a total of 173 lesions excised of which 123 were a non-melanoma skin cancer (NMSC) (108 basal cell carcinomas (BCCs) and 15 squamous cell carcinomas (SCCs)). None of these lesions had any high-severity features such as poor differentiation or lymphovascular invasion. Numbers of BCCs have not varied, but numbers of SCCs, Bowen's disease and Actinic Keratoses have risen gradually over time. Discussion: The patient developed his first skin cancer later than has typically been reported in transplant patients and has had a ratio of BCCs to SCCs more similar to the non-transplant population. Conclusion: Whilst the patient has had a large number of NMSCs over time, a recognised association for those taking immunosuppressive medications, the types and nature of his lesions mirrored that of the non-transplant population, which could relate to the fact he received his transplant as a child.